Effects of sugar mill lime sludge treatment on the CBR and UCS of expansive soil in Bukidnon - Daleon, Cheryl F. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2017)
The purpose of this study is twofold: to address the proper utilization and disposal of a locally available industrial waste known as sugar mill lime sludge, and to determine whether it could improve the subgrade performance of an expansive clay by evaluating its California Bearing Ratio (CBR) and Unconfined Compressive Strength (UCS). The expansive soil known as Adtuyon clay from Stockfarm, Dalwangan was treated with lime sludge contents of 0%, 5%, 10%, 15%, 20%, 25%, and 30% (all by dry weight of soil); the specimens from each of these mixing conditions were cured at 0, 7, 14, and 28 days. Results show that the treated soil with 10% lime sludge and curing period of 28 days demonstrated a higher CBR and UCS. On the other hand, treated soils with lime sludge contents above and below 10% regardless of curing periods have indicated lower CBR and UCS values, thus yielding inferior engineering properties. Therefore, the expansive clay in Bukidnon can be stabilized using the locally available sugar mill lime sludge at an optimum lime sludge content of 10% cured at a minimum curing period of 28 days.